John Steinbeck in Berlin - unknown:::Creator::::::::::::
John Steinbeck meeting with (from left to right) Guenter Grass, Hans Scholz, and Ralph Brown (US Mission Political Officer) at Minister John A. Calhoun's residence in Berlin, Germany.